Effect of ATC Understanding of Cockpit Procedures on Performance in Jakarta ATSC ACC Unit - Miftahul Awaludin Jasmin; Emilia Rahajeng Larasati; Lina Rosmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Aviation safety is a fundamental priority in modern air transportation systems, where effective communication and coordination between pilots and Air Traffic Controllers (ATCs) are essential. This study aims to examine the effect of ATC understanding of cockpit procedures through Flight Simulator media on ATC performance at the Area Control Centre (ACC) Unit of Jakarta Air Traffic Services Center (JATSC), operated by Perum LPPNPI (AirNav Indonesia). The research employed a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 69 active ATCs working at the ACC unit. The research instruments were developed based on indicators of cockpit procedure understanding and ATC performance and were tested for validity and reliability. Data analysis was conducted using descriptive statistics, prerequisite testing, and Kendall’s Tau correlation analysis to examine the relationship between variables. The results show that both the level of ATC understanding of cockpit procedures and ATC performance are generally high. Furthermore, the analysis indicates a positive and significant relationship between understanding cockpit procedures and ATC performance. In conclusion, enhanced comprehension of cockpit procedures through simulator-based training contributes to improved ATC performance and supports operational effectiveness and aviation safety within the Jakarta Flight Information Region